Reviewer Acknowledgements for Business Management and Strategy, Vol. 15, No. 2 - Lee, Jean (Business Management and Strategy, 2024)
reviewers for their assistance with peer review of manuscripts for this issue. Many authors, regardless of whether BMS publishes their work, appreciate the helpful feedback provided by the reviewers. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Each of the reviewers listed below returned at least one review for this issue. Reviewers for Volume 15, Number 2 Agha Usama Hasan, University of West London, UK Fakhrul Hasan, Northumbria University, UK Halimahton Borhan, Universiti Teknologi Mara, Malaysia Izabella Manukyan, Russian-Armenian University, Armenia Kazunori Minetaki, Kindai University, Japan Nicholas Renaldo, Institut Bisnis dan Teknologi Pelita Indonesia, Indonesia Nicoleta Nicoleta Dospinescu, Alexandru Ioan Cuza University, Romania Saeid Nasrollahi, Sepahanlifter Company, Iran Soolakshna Lukea Bhiwajee, University Of Technology, Mauritius, Mauritius Jean Lee Business Management and Strategy Macrothink Institute ************************************* Add: 5348 Vegas Dr.#825 Las Vegas, Nevada 89108 United States Tel: 1-702-953-1852 ext.508 E-mail1: bms@macrothink.org E-mail2: bms@macrothink.com Website: http://bms.macrothink.org